The Accuracy of Custom-Made Milled Metal Posts as Compared to Conventional Cast Metal Posts - Tabarak M. AL-Rubaye; Emad S. Elsubeihi (MDPI AG, 2024)
Aim: The aim of this study was to compare the fitting accuracy of custom-made metal posts and cores fabricated by half-digital and milling technique to that of conventional cast posts fabricated by direct technique. Methods: Sixteen extracted single-rooted teeth were endodontically treated followed by post space preparation. A direct resin post and core pattern was made for each tooth and used for the fabrication of two posts (n = 16). Each post resin pattern was digitized with a laboratory scanner and used for the fabrication of a milled cobalt-chrome (Co-Cr) alloy post, while the direct resin pattern, after scanning, was cast in a Co-Cr alloy to produce a cast post. Each post was seated on its respective tooth and evaluated using microcomputed tomography. The following variables were evaluated: total space volume between the post and root canal, the volume and distance of the apical gap between each post and the remaining apical root canal filling, as well as the distance and surface area of the space between the post and lateral root canal wall at four determined points along the length of each post. Results: The results revealed that half-digital and milled posts had a statistically significantly higher total space volume (p < 0.05), apical gap volume (p < 0.02) and distance (p < 0.02), as well as a higher surface area of space between the post and root canal wall at the cervical area as compared to the cast post (p < 0.05). Conclusions: This study demonstrated that the fitting accuracy of cast posts was more accurate than posts fabricated with half-digital and milling technique.